Impact of Various Joint Designs on the Transverse Strength of Heat-Cured Acrylic Resin Repairs - shallal, Waleed; Alsaffar, Mohammed Qasim; Hafith, Aseel Niema (American Journal of Biomedicine and Pharmacy, 2024)
Statement of Problem: The fracture of complete denture is a common occurrence in the field of prosthodontics. Often if all other criteria are met such as good aesthetics, occlusion, and functionality; denture repair is acceptable. Once denture fractures, we would want the joint surface strength to be as good as original. Purpose: The purpose of this study was to determine the effect of different surface design on the transverse strength of repaired acrylic denture resin. Materials and Methods: Forty specimens of heat-cured acrylic resin of dimension 65 mm× 10 mm× 2.5 mm (length, width, and thickness respectively), 8 of them were kept intact and considered as a control group. 32 samples were cut at the middle with (3mm) and prepared with different joint designs as butt, round, grooves for wire embedding (0.7 mm), and beveled (each of them have 8 samples). Transverse strength of four joint contours was then compared with control group and also they were compared with each other and result was statistically analyzed with one-way analysis of variance (ANOVA) and LSD. Result: Result of transverse strength test showed that the highest mean value recorded by wire embedding group which equal to (91.715), while the lowest mean value represented by round group which equals to ( 55.605). Conclusion: Methods of repair have significant effect on transverse strength of repaired denture. Wire joint design of repair technique was far superior among all studying groups.